Effects of dendritic segregation and local internal stress on microstructure evolution in a 3rd-generation single crystal superalloy during thermal exposure - Yabo Liu; Yang Li; Zhiran Yan; Donghai Yu; Chenlong Liang; Ming Xue; Changjian Geng; Ru Su; Shilei Li; Lunhua He; Yan-dong Wang (Materials & Design)
The inevitable dendritic segregations in single crystal superalloys pose a serious challenge to the microstructural stability and mechanical reliability. This study systematically examines how composition segregation and local internal stresses at the dendritic scale affect γ′ phase rafting and topologically close-packed (TCP) phase precipitation, along with relevant lattice misfit evolution during thermal exposure at 1000 °C and 1100 °C in a 3rd generation single crystal superalloy. The results demonstrate the disparity of rafting kinetics at the dendritic scale, originating from synergistic effect of dendritic stresses and enhanced lattice misfit magnitude within the dendrites due to chemical segregation. The dendritic stresses rather than chemical gradients dictate the heterogeneous γ′ rafting orientations across dendritic structure at 1100 °C. Furthermore, the TCP phases preferentially nucleated at dendritic junctions with complex stress fields facilitating dislocation multiplication and elemental segregation, contrary to conventional observations. A comparison of lattice parameters and misfit along growth axial (AD) and transverse (TD) directions based on neutron diffraction unveils that the discrepancies between AD and TD, attributed to macroscopic internal stress, persisted at 1000 °C but gradually diminished at 1100 °C. This phenomenon indicates that coherency stress relaxation through γ/γ′ interfacial dislocation formation can accommodate multi-scale internal stress of alloys.